HABITUS PEMBALAK LIAR PADA MASYARAKAT KETAMBE KABUPATEN ACEH TENGGARA - Al Bahri, Muhammad; Nirzalin, Nirzalin (FISIP Universitas Malikussaleh, 2020)
This research discuss about the â€œIllegal Logging Habitus in Ketambe Community, Aceh Tenggara Districtâ€. The purpose of this research is to know and understand how illegal logging practices, the process of socializing illegal logging habits and why illegal logging practices are still carried out even though the community already knows the risks will have implications for natural disasters. This research was conducted in Ketambe District, Aceh Tenggara District, Aceh Province. This study uses the Habitus theory developed by Pierre Bourdieu. This study used a qualitative descriptive approach, the data in this study were collected through observation, interviews, and documentation. The results of this study explain that the practice of illegal logging in Ketambe Subdistrict, Aceh Tenggara District is carried out systematically by timber shopkeepers who have the capital and strategic positions as figures in society and their relationships with unscrupulous state apparatus and provide gratification to these State officials in order to maintain their business. in the logging sector. The socialization of habitus to illegal logging in the ketambe community through transformation results from empirical experiences by being heard, shown, and taught to act so that in order to survive, they are taught with explanations of how to act as loggers. As well as the motive that encourages people to continue to carry out illegal logging actions is a pragmatic perspective about obtaining economic benefits in a short time coupled with very limited decent work opportunities so that it encourages the action to continue continuously so that they can survive in the era of modernization and globalization which is all complexABSTRAKPenelitian ini mengkaji tentang â€œHabitus Pembalakan Liar pada Masyarakat Ketambe Kabupaten Aceh Tenggaraâ€. Tujuan studi ini adalah mengetahui dan memahami praktik pembalakan liar, proses sosialisasi habitus pembalakan liar, dan alasan praktik ini tetap dilakukan meskipun diketahui resikonya akan berimplikasi pada bencana alam. Penelitian dilakukan di Kecamatan Ketambe Kabupaten Aceh Tenggara. Studi ini menggunakan teori habitus yang dikembangkan oleh Pierre Bourdieu. Pendekatan penelitian yaitu deskriptif kualitatif, dimana data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menemukan bahwa praktik pembalakan liar di Kecamatan Ketambe Kabupaten Aceh Tenggara dilakukan secara sistematis oleh para toke kayu yang memiliki modal. Mereka memiliki posisi sosial yang strategis sebagai tokoh masyarakat dan memiliki relasi dengan oknum aparatur negara. Gratifikasi diberikan kepada oknum aparatur negara agar dapat mempertahankan kelangsungan usahanya. Sosialisasi habitus pembalak liar pada masyarakat Ketambe melalui transformasi hasil dari pengalaman empiris dengan cara diperdengarkan, diperlihatkan, dan diajarkan untuk bertindak sehingga agar bisa bertahan hidup maka mereka diajarkan dengan penjelasan-penjelasan tentang bagaimana cara untuk bertindak sebagai pembalak. Motif yang mendorong masyarakat untuk tetap melakukan tindakan pembalakan liar bersifat pragmatis yaitu memperoleh keuntungan ekonomi dalam waktu singkat ditambah dengan keterbatasan lapangan pekerjaan sehingga hal tersebut mendorong tindakan tersebut tetap berlangsung secara terus-menerus